Life cycle and reproductive potential of the predator ant Solenopsis cf. picea (Hymenoptera: Formicidae) - HERRERA-RANGEL, JANINE; ARMBRECHT, INGE (Revista Colombiana de Entomología, 2007)
Solenopsis cf. picea, also known as “the little black”, is an abundant ant in the coffee systems of Risaralda, Colombia, where it nests in the soil and can be found in both shaded coffee plantations and in coffee monocultures. Studies carried out in the field and laboratory have demonstrated that it predates on the coffee berry borer, making it an organism that could be implemented as a biological control. The objective of this research was to study some aspects of its life cycle, in terms of development of the immature and reproductive aspects of the organism. Results showed that immature development (chronological and morphological recognition) took an average of 56 days. The cephalic capsule measures grouped individuals into three larval instars. Mean number of eggs laid in 24 hours was significantly higher in monogynous colonies accompanied by high densities of workers, and the individual fecundity of the queens decreased with the presence of other queens in the same colony.